Teacher-Student Relationship to Emotional Well-Being, Motivational Learning, and Academic Performance - Ajeng Kusumawardani; Hani Yulindrasari; Tina Hayati Dahlan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study explores teacher-student relationships (TSR) and their impact on students' emotional well-being, learning motivation, and academic performance. Through a literature review, this study identified that positive teacher-student relationships, involving empathy, emotional support, and effective communication, play a significant role in creating an inclusive and supportive learning environment. Good emotional connections between teachers and students can reduce emotional distress, increase intrinsic motivation, and promote students' academic success. The results of the analysis showed that TSR contributed to improving emotional well-being, encouraging prosocial behavior, and strengthening students' self-confidence and engagement in learning. The study also highlights the challenges faced in building positive TSR, including less inclusive teaching approaches and differences in student characteristics. As a solution, the study recommends training for teachers in managing emotions and empathy, as well as implementing learning strategies that support active student engagement. By understanding the importance of TSR, it is hoped that educators can create more holistic and inclusive educational policies and practices, which ultimately contribute to better quality education in Indonesia.